Cudzoziemcy jako sprawcy przemytu zabytków – wybrane aspekty kryminologiczne - Perkowska, Magdalena (Studia Prawnoustrojowe, 2019)
Any loss in the field of relic are very harmful for the national heritage of every country. Poland is an important actor on the European political and geographical map in the area of goods smuggling, also the relics smuggling. Therefore the article presents the dogmatic analysis of crime of relict smuggling. Article also presents the results on scientific criminological research. This is the results of analysis of criminal court records of foreigners convicted for relics smuggling in Poland.